(untitled) (Journal of Hama University, 2022)
This study aimed to determine The effect of aqueous Nigella sativa seeds extract on level s of FT3,FT4,TSH in the blood serum of induced oral hypothyroidism White adult mice and promoting it’s therapeutic capacity . This study included 30 female white mice( Balb/c strain )which were divided into three experimental group ,10 mice in each :the first group was the physiological control was treated with oral cavity 0,9% Nacl until the end of the experiment, While the second group was the pathologyical control was treated with oral cavity of methimazole in dose (0,05mg/kg) for three weeks,and, the third group was treatment group were treated whith cavity of 400mg/kg aqueous extract of nigella sativa for4 weeks .at the end of experiment e blood simplees were collected for biochemical analysis. Result showed that the aqueous extract of nigella sativa seeds has positive effect on hypothyroidism ,as the level of FT3 were significantly increase(p<0.05) and nonsignificantly increase in level of FT4 ,as well as significantly decreas (p<0.05) in level of TSH by it’s effect.